Molecular classification of grade 3 endometrioid endometrial cancers identifies distinct prognostic subgroups - Bosse, Tjalling (Am J Surg Pathol, 2018)
Our aim was to investigate whether molecular classification can be used to refine prognosis in grade 3 endometrioid endometrial carcinomas (EECs). Grade 3 EECs were classified into four subgroups: p53-abnormal, based on mutant-like immunostaining (p53abn); MMR-deficient, based on loss of mismatch repair protein expression (MMRd); presence of POLE exonuclease domain hotspot mutation (POLE); no specific molecular profile (NSMP), in which none of these aberrations were present. Overall (OS), and recurrence-free survival (RFS) rates were compared using the Kaplan-Meier method (Log-Rank test) and univariable and multivariable Cox proportional hazard models. In total, 381 patients were included. The median age was 66 years (range 33–96). FIGO stages (2009) were as follows: IA, 171 (44.9%), IB, 120 (31.5%), II, 24 (6.3%), III, 50 (13.1%), IV, 11 (2.9%). There were 49 (12.9%) POLE, 79 (20.7%) p53abn, 115 (30.2%) NSMP, and 138 (36.2%) MMRd tumors. Median follow-up of patients was 6.1 years (range 0.2–17.0). Compared to patients with NSMP, patients with POLE mutant grade 3 EEC (OS: Hazard Ratio [HR] 0.36 [95%CI: 0.18–0.70], p=0.003; RFS: HR 0.17 [0.05–0.54], p=0.003) had a significantly better prognosis; patients with p53abn tumors had a significantly worse RFS (HR 1.73 [1.09–2.74], p0.021); patients with MMRd tumors showed a trend towards better RFS. Estimated 5-year OS rates were as follows: POLE 89%, MMRd 75%, NSMP 69%, p53abn 55% (Log Rank p=0.001). Five-year RFS rates were as follows: POLE 96%, MMRd 77%, NSMP 64%, p53abn 47% (p=0.000001), respectively. In a multivariable Cox model that included age and FIGO stage, POLE and MMRd status remained independent prognostic factors for better RFS; p53 status was an independent prognostic factor for worse RFS. Molecular classification of grade 3 EECs reveals that these tumors are a mixture of molecular subtypes of endometrial carcinoma, rather than a homogeneous group. The addition of molecular markers identifies prognostic subgroups, with potential therapeutic implications.